Reflections of Memory in Georg Guðni´s Artistic Work - Mathlin, Mari Anniina, 1980- (2014)
The text focusses on the importance of memory in the art practice of Georg Guðni and the role memory plays when his works are perceived by an audience. The subject of memory is approached by examining the background and premises of Georg Guðni´s working process, which is a major part of the artist´s personal history. Georg Guðni´s experiences in nature became exposed to both to art history and the spirit of the art world during his studies in Reykjavík and Holland in the 1980s. During this time the definition of memory affected and shaped the artist´s thinking and his work. In contrast, to the Icelandic landscape tradition, which concerned itself with the depiction of specific natural environments, Georg Guðni´s paintings created a totally new, unseen space for us to encounter, by and through his memory as well as ours.